Bring your own digital device in teacher education - Newhouse, C.; Cooper, Martin; Pagram, J. (Routledge, 2015)
This article reports on an investigation to advise a teacher education institution on the feasibility of having a “Bring Your Own Digital Device” policy for students. The investigation built on components of two research projects while adding the comprehensive testing of representative potential hardware and software platforms. The initial emphasis was on identifying the digital technology demands of our teacher education courses. A representative range of potential devices was tested against these demands. At the time of testing, all laptop devices were found to be adequate but only the iPad was adequate in the mobile range. In a survey of a sample of students, nearly all owned an appropriate device but most made limited, if any, use of it at the university.